Formulasi Gel Peel Off Pewarna Kuku yang Mengandung Ekstrak Daun Pacar Air (Impatiens balsamina L.) dan Sodium Carboxy Methyl Cellulose - Teti Indrawati; Titih Ayunda Larasati; Anggun Nia Mulyani; Desy Muliana Wenas (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Leaves of Pacar air or Impatiens balsamina L. (IB) are directly pounded and then placed on the surface of the nail to color the nails traditionally. It’s preferred by Moslem because wudu water can penetrate to the nail. The traditional way of using the leaves is unpleasant and these leaves should be used in the fresh form. The IB leaves contain fl avonoids, quinones and tannins that provide a natural orange color. A formulation of a nail polish containing the leaf’s extract is needed so it’s easy to use and stable during storage. The aim of this research is to make nail color gel peel off from IB extract which is easy to use and stable. Nail color gel peel off is made using Sodium Carboxy Methyl Cellulose (Na-CMC) as a gel base. This research was carried out by making six formula of gel peel off using swelling and mixing methods at various IB extract concentrations of 5%, 10% and 15% using 1% and 3 % of Na-CMC as the base respectively and the prepared product was evaluated. The IB leaves can be made into cosmetic preparations that have a good quality. All preparations have a yellow to orange red, odorous and homogeneous, pH 4.7-5.4, viscosities 630-3600 cps, has a pseudo plastic thixotropic fl ow properties. When nail color gel peel off used in nails, the base can remove from nail and only the coloring agent attached to the nail.